The political influence of the Cromwellian army in Ireland, 1649-1659 - Higgins Ní Chinnéide, Caitlín (Trinity College (Dublin, Ireland). Department of History, 2013)
This thesis examines the political role of the Cromwellian army in Ireland during the interregnum of 1649 to 1660. Despite the importance of this institution, it has received relatively little treatment in the historiography, particularly from a political perspective; this thesis seeks to address this gap. In doing so, it examines how the Cromwellian army in Ireland evolved politically; influenced legislation in Ireland; and played an important role in the government both at local and national levels. It will also explore how changes in government in England and Scotland were regarded by the army in Ireland during this period and to what extent it participated in or reacted to these changes. It will consider how and why the army's political power was diminished when Henry Cromwell replaced Charles Fleetwood as the de facto governor of Ireland in 1655 and whether disaffection engendered at this time, in Ireland and across England and Scotland, affected the long-term viability of the Cromwellian regime.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin